2019
DOI: 10.1089/omi.2019.0039
|View full text |Cite
|
Sign up to set email alerts
|

Global Proteome Profiling Reveals Drug-Resistant Traits in Elizabethkingia meningoseptica: An Opportunistic Nosocomial Pathogen

Abstract: Elizabethkingia meningoseptica is Gram-negative, rod-shaped opportunistic bacterial pathogen increasingly reported in hospital-acquired outbreaks. This bacterium is well known to thrive in the hospital environment. One of the leading causes of meningitis in pediatric and immune-compromised patients, E. meningoseptica has been noted as a ''pathogen of interest'' in the context of nosocomial diseases associated with device-related infections in particular. This pathogen's multidrug-resistant phenotype and attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Multiple resistance genes and drug efflux systems in Elizabethkingia have been demonstrated by genomic and proteomic analysis. 35,36 In this study, the high carriage rate of bla CME , bla BlaB and bla GOB genes was consistent with the broad-spectrum resistance to β-lactams including carbapenems. Nevertheless, piperacillintazobactam and cefoperazone-sulbactam were active in vitro against Elizabethkingia, in accordance with the results of a previous study where both combinations showed reasonable in vitro activity (70-85% and 65-80% of susceptibility rate, respectively) against 170 clinical Elizabethkingia isolates in China.…”
Section: Discussionsupporting
confidence: 74%
“…Multiple resistance genes and drug efflux systems in Elizabethkingia have been demonstrated by genomic and proteomic analysis. 35,36 In this study, the high carriage rate of bla CME , bla BlaB and bla GOB genes was consistent with the broad-spectrum resistance to β-lactams including carbapenems. Nevertheless, piperacillintazobactam and cefoperazone-sulbactam were active in vitro against Elizabethkingia, in accordance with the results of a previous study where both combinations showed reasonable in vitro activity (70-85% and 65-80% of susceptibility rate, respectively) against 170 clinical Elizabethkingia isolates in China.…”
Section: Discussionsupporting
confidence: 74%
“…Elizabethkingia isolates were frequently resistant to many antimicrobial agents, including most β-lactams and inhibitors, aminoglycosides, macrolides, tetracycline, vancomycin, and carbapenems (25). They exhibited variable susceptibility to piperacillin, piperacillin-tazobactam, uoroquinolones, minocycline, tigecycline, and trimethoprim-sulfamethoxazole(26).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological reports related to E. meningoseptica infection show that Taiwan had the highest number of reported cases, with a mortality rate of 63.2% [3]. Reports from South Korea, Spain, the United Kingdom, India, and Taiwan show that E. meningoseptica can survive in hospital sinks, faucets, humidi ers, and other ward environments and on medical equipment and can cause nosocomial outbreaks [20][21][22][23]. These ndings and the broad resistance of E. meningoseptica in our hospital indicate that E. meningoseptica infection is a serious threat to people's health and lives; furthermore, the possibility that serious nosocomial infections may recur in speci c populations, such as ICU patients or those with weakened immunity, cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%